<span>x2 +8x +4y +4 = 0
</span>4y=<span> -x2 -8x -4</span>y = -.25*x^2 -2x -1
a = -.25b = -2c = -1
x position of vertex:
h = -b / 2a
h = 2 / 2*-.25h = 2 / -.5h = -4
y position of vertex:
k = ah^2 + bh + ck = -.25*-4^2 + -2*-4 + -1k = -4 +8 -1k = 3
VERTEX = (-4, 3)**************************************************************************
x value of focus =x value of vertex = -4
y value of focus =(1 (-b^2 -4ac)) / 4a
a = -.25 b = -2 c =-1
y value = (1 (-4 -4*-.25*-1)) / 4*-.25
y value = (1 (-4 -4*-.25*-1)) / -1
y value = (1 -4 +1) / -1y value = (-2 / -1)y value = 2
focus value = (-4, 2)
Answer is the last one.
Answer:
incomplete
Step-by-step explanation:
please send the full information, I can't see students belonging to acers
The number of messages Kaitlyn, Tony and Austin sent are 13, 18 and 72 messages respectively.
<h3>How to write and solve equation?</h3>
let
- Number of messages Kaitlyn sent = x
- Number of messages Tony sent = x + 5
- Number of messages Austin sent = 4(x + 5)
- Total messages = 103
103 = x + (x + 5) + 4(x + 5)
103 = x + x + 5 + 4x + 20
103 = 6x + 25
103 - 25 = 6x
78 = 6x
x = 78/6
x = 13
Number of messages each sent:
Number of messages Kaitlyn sent = x
= 13 messages
Number of messages Tony sent = x + 5
= 13 + 5
= 18 messages
Number of messages Austin sent = 4(x + 5)
= 4(13 + 5)
= 4(18)
= 72 messages
Learn more about equation:
brainly.com/question/2972832
#SPJ1
THE EQUATION TO THIS PROBLEM IS y=2x+12
Answer:
(16x + 21) and (16x - 6)
Step-by-step explanation:
f(g(x)) = f(6 + 4x)
Applying the f(x) function on (6 + 4x) gives
4(6 + 4x) - 3
Which equals 16x + 24 - 3
= 16x + 21
g(f(x)) = g(4x - 3)
Applying the g(x) function on (4x - 3) gives
6 + 4(4x - 3)
Which equals 6 + 16x - 12
= 16x - 6